Exposure to the 1959-1961 Chinese famine and risk of non-communicable diseases in later life: A life course perspective - Mengling Cheng; Nicolas Sommet; Marko Kerac; Daniela S. Jopp; Dario Spini (Public Library of Science (PLoS), 2023)
Child undernutrition and later-life non-communicable diseases (NCDs) are major global health issues. Literature suggests that undernutrition/famine exposure in childhood has immediate and long-term adverse health consequences. However, many studies have theoretical and methodological limitations. To add to the literature and overcome some of these limitations, we adopted a life course perspective and used more robust methods. We investigated the association between exposure to the 1959-1961 Chinese famine and later-life NCDs and if this association depends on: life stage at exposure, famine severity, and sex. We conducted a secondary data analysis of a large-scale, nationally representative, longitudinal study-the China Health and Retirement Longitudinal Study (2011-2018, 11,094 participants). We measured famine exposure/severity using self-reported experience, life stage using age at exposure, and health using the number of NCDs. We performed Poisson growth curve models. We obtained three findings. First, compared with unexposed participants, those exposed before age 18 had a higher risk of later-life NCDs, particularly if exposed in-utero (IRR = 1.90, 95% CI [1.70, 2.12], p < .001) and in the "first 1,000 days" of life (IRR = 1.86, 95% CI [1.73, 2.00], p < .001; for 0-6 months group, IRR = 1.95, 95% CI [1.67, 2.29], p < .001). Second, the famine effects among participants moderately and severely exposed were similar (IRR = 1.18, 95% CI [1.09, 1.28], p < .001 and IRR = 1.24, 95% CI [1.17, 1.32], p < .001). Third, the famine effects did not differ between females and males (IRR = 0.98, 95% CI [0.90, 1.07], p = .703). In an individual's life course, in-utero and the "first 1,000 days" are a particularly sensitive time period with marked long-term implications for NCDs if undernutrition/famine is experienced in this period. However, this window remains open until young adulthood. This highlights the need to invest more in preventing and treating child/adolescent undernutrition to tackle later-life NCDs.